Community perception regarding rabies prevention and stray dog control in urban slums in India - Mrudu Herbert; Riyaz Basha S; Selvi Thangaraj (Elsevier, 2012)
Summary: Background: The lack of community awareness about rabies control is a major issue that thwarts efforts to prevent human deaths caused by rabies.The objectives of this study were (1) to assess community knowledge and attitudes about rabies, rabies prevention and stray dog control in an urban slum community and (2) to determine the factors that influence rabies awareness in urban slums. Methodology: Using a systematic random sampling strategy, 185 participants were selected from 8 urban slums. The data were collected by direct interview using a pre-tested, structured questionnaire. Results: In the study population, 74.1% of the participants had heard about rabies, and 54.1% knew that rabies is a fatal disease. Only 33.5% of the interviewees felt that people in the community had a role to play in controlling the stray dog population. Gender, age and educational status were significantly associated with rabies awareness. Conclusions: Our study indicates that there are gaps in the knowledge and attitudes of individuals living in urban slums regarding rabies prevention and control. Efforts to promote awareness should be targeted at men, older people and uneducated individuals. Keywords: Rabies, First aid, Stray dog, Animal control